Об’єкт насильства над населенням у районі воєнних дій (ст. 433 КК України) - Мухамеджанова, А. Р.; Mukhamedzhanova, A. R. (Проблеми правознавства та правоохоронної діяльності. - 2016. - № 3(57). - С. 85-94, 2016)
Проаналізовано доктринальні підходи щодо визначення та змісту родового об’єкта злочинів проти встановленого порядку несення військової служби (військові злочини). Визначено основний безпосередній об’єкт насильства над населенням у районі воєнних дій, а також додаткові об’єкти цього злочину.

The paper touches upon analyzing of doctrinal approaches to definition of generic and direct (basic and additional) object of violence against a population within an area of military activities (art. 433 of Penal Code of Ukraine) as a crime against a provided order of doing military service (military crime). It has been established that in the fullest detail the generic object of military crimes, which are provided by the Chapter XIX of Penal Code of Ukraine, can be defined as social relations in the field of protection of and order of doing military service in accordance with effective legislation and the other legal acts of Ukraine. To the author`s point of view this definition adequately reflects protective function of penal law concerning securing of order of doing military service as a special government service including all its fields (serving and doing). The basic and direct object of violence against a population within an area of military activities is, under the author`s suggestion, social relations in the field of doing military service, namely in the field of protecting civilians from illegal actions of Armed Forces of Ukraine military servants and the other military groups which were established under the laws of Ukraine and which are in the territory of military activities or armed conflict (order of doing military service and ensuring civilian security). As additional obligatory objects of the infringement referred to above (depending on the form of socially dangerous action) we can regard social relations in the field of securing human life and health and (or) social relations in the field of property rights securing.

Проанализированы доктринальные подходы к определению и содержанию родового объекта преступлений против установленного порядка несения воинской службы (воинские преступления). Определен основной непосредственный объект насилия над населением в районе военных действий, а также дополнительные объекты этого преступления.
Target of violence against the population in war zones (Art. 433 of the Criminal Code of Ukraine)
Объект насилия над населением в районе военных действий (ст. 433 УК Украины)
Мухамеджанова, А. Р. Об’єкт насильства над населенням у районі воєнних дій (ст. 433 КК України) / Мухамеджанова Аліна Равілівна // Проблеми правознавства та правоохоронної діяльності. - 2016. - № 3(57). - С. 85-94.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; військові злочини; war crimes; военные преступления; безпека цивільних осіб; safety of civilians; безопасность гражданских лиц; військова служба; military service; военная служба; об’єкт злочину; object of the crime; объект преступления; порядок несення військової служби; order of military service; порядок несения военной службы; об’єкт насильства над населенням; цивільне населення